2011
DOI: 10.4236/msa.2011.29173
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nano Size TiO<sub>2</sub> Particles on Mechanical Properties of AWS E 11018M Type Electrode

Abstract: Addition of nano size particles of TiO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…The oxygen in turn may provide stirring effect to the weld pool. This will lead to enhanced recovery of alloying elements in the weld pool (Pal and Maity, 2011) and thus prevent the formation of oxides or fumes.…”
Section: Constituent Analysis Of Fumesmentioning
confidence: 99%
“…The oxygen in turn may provide stirring effect to the weld pool. This will lead to enhanced recovery of alloying elements in the weld pool (Pal and Maity, 2011) and thus prevent the formation of oxides or fumes.…”
Section: Constituent Analysis Of Fumesmentioning
confidence: 99%
“…Another way for obtaining better properties, especially in microstructure, is to input various elements into the puddle to improve hardness, toughness, penetration, and other properties of weld [2][3][4]. In this way, typical materials, micro-particles, and nanoparticles can be used [5][6][7][8]. It has been shown that in the SAW process, hardness decreases by adding TiO 2 nanoparticles to the weld pool [9].…”
Section: Introductionmentioning
confidence: 99%
“…The other influence was improved the tensile strength and impact toughness properties of the welding zones due to the ultrafine grain size of the ferrite for the reheated zones [14]. Pal et al used [15].…”
Section: Introductionmentioning
confidence: 99%
“…The electrode coating by TiO 2 NPs achieved improving in mechanical properties of the weld zones [14,15]. In this paper, the effect of TiO 2 NPs on the Impact toufghness, the nucleation of intragranular ferrite, and microstructure of weld metals will be carried out in investigated using the cold spray coating method to add nanoparticles on welding joints.…”
Section: Introductionmentioning
confidence: 99%